2021
DOI: 10.1111/pce.14127
|View full text |Cite
|
Sign up to set email alerts
|

A poplar B‐box protein PtrBBX23 modulates the accumulation of anthocyanins and proanthocyanidins in response to high light

Abstract: Flavonoids, which modulate plant resistance to various stresses, can be induced by high light. B-box (BBX) transcription factors (TFs) play crucial roles in the transcriptional regulation of flavonoids biosynthesis, but limited information is available on the association of BBX proteins with high light. We present a detailed overview of 45 Populus trichocarpa BBX TFs. Phylogenetic relationships, gene structure, tissuespecific expression patterns and expression profiles were determined under 10 stress or phytoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 109 publications
1
24
0
Order By: Relevance
“…In other species, some BBXs were involved in regulating the synthesis of anthocyanins, such as the BBX33/CONSTANS-like 11 ( COL11 ) gene which controls the expression of MYB10 in apple fruit, thereby affecting the synthesis of anthocyanins and regulating the color of the red skin ( Plunkett et al, 2019 ). The overexpression of BBX23 in poplars ( Populus trichocarpa ) activates the expression of MYB transcription factors and structural genes in the flavonoid pathway, thereby promoting the accumulation of procyanidins and anthocyanins ( Li et al, 2021 ). In this study, the CaBBX gene family was systematically studied by both RNA-seq and qRT-PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other species, some BBXs were involved in regulating the synthesis of anthocyanins, such as the BBX33/CONSTANS-like 11 ( COL11 ) gene which controls the expression of MYB10 in apple fruit, thereby affecting the synthesis of anthocyanins and regulating the color of the red skin ( Plunkett et al, 2019 ). The overexpression of BBX23 in poplars ( Populus trichocarpa ) activates the expression of MYB transcription factors and structural genes in the flavonoid pathway, thereby promoting the accumulation of procyanidins and anthocyanins ( Li et al, 2021 ). In this study, the CaBBX gene family was systematically studied by both RNA-seq and qRT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…spp. ), BBX23 directly binds to the promoter regions of proanthocyanidins and anthocyanin-specific genes and interacts with HY5 to enhance their activation ( Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that BBX group IV proteins containing two tandem repeat B-box domains, but no CCT domain, can act as either positive or negative regulators of light-induced anthocyanin biosynthesis in plants [ 24 , 36 , 50 , 51 ]. In addition, some BBX group V proteins contain only one B-box domain, such as AtBBX32 in Arabidopsis [ 33 ] and MdBBX37 in apple [ 40 ], and are involved in negatively controlling anthocyanin accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, studies have confirmed that the expression of the structural genes mentioned above has different degrees of synergy, which is directly controlled by the MBW complex formed by MYB, bHLH, and WDR transcription factors (TFs) [ 13 , 18 , 19 ]. In addition to the MBW complex, several TFs, such as DELLA, JAZ, COP1, PIF3, SPL, WRKY, B-box protein, and bZIP, have been reported to regulate anthocyanin biosynthesis via interaction with the MBW complex, or acting on the upstream of the MBW complex [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. In addition, some external environmental factors can also induce anthocyanin biosynthesis, such as light, temperature, and drought [ 22 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the MBW complex, several TFs, such as DELLA, JAZ, COP1, PIF3, SPL, WRKY, B-box protein, and bZIP, have been reported to regulate anthocyanin biosynthesis via interaction with the MBW complex, or acting on the upstream of the MBW complex [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. In addition, some external environmental factors can also induce anthocyanin biosynthesis, such as light, temperature, and drought [ 22 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%